Features of takeoff phase in long jumps with various run-up lengths - Nemtsev, O.; Doronin, A.; Nemtseva, N.; Sukhanov, S.; Shubin, M. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The aim of the present study was to compare the kinematic characteristics of jumper's movements in long jumps with short, middle and extended run-ups. For this purpose three male and four female jumpers performed two three strides, eight strides and twelve strides run-up long jumps. All trials were captured on high-speed video. The results of the 2D analysis indicated that ground contact time and takeoff angle were significantly larger when the run-up was short. Also, the distance from the center of gravity to the heel in the horizontal plane and the knee angle at touchdown, as well as the maximum knee flexion of the takeoff leg during takeoff, were significantly smaller when the run-up was short. The heights of the center of gravity at touchdown and takeoff were constant in long jumps with various run-up lengths.